A laparoscopic transgastric approach to the treatment of sphincter of Oddi dysfunction postgastric bypass. (22nd May 2013) - Dickinson, Karen J; Beckett, Conrad G; May, John C; Halstead, James C
Abstract : Obesity is endemic and bariatric surgery is increasing in an attempt to reduce the physiological and social cost. As the prevalence of bariatric surgery increases, in particular laparoscopic roux-en-Y gastric bypass (LRYGB), the need to investigate and treat subsequent pathology in the gastric remnant and biliary tree will accrue. We describe a novel combined surgical and endoscopic technique addressing the challenges of postoperative anatomy, allowing investigation and treatment of the gastric remnant and biliary tract. We present the case of a patient with sphincter of Oddi dysfunction post-LRYGB who underwent laparoscopic transgastric endoscopic injection of Botox into the ampulla with an excellent symptomatic relief. Subsequent laparoscopic transgastric sphincterotomy allowed definitive treatment and allowed symptom resolution at 6 months follow-up. Laparoscopic transgastric endoscopic investigation and treatment is a novel approach to circumvent the restrictions of post-LRYGB anatomy and may assume greater importance in an ageing obese population.